Careers Mom vs. Bomb. - Karlin, S. (IEEE spectrum)
This paper discusses the development of a robot that has the ability to detect, inspect, and neutralize bombs. Its success is proved by saving lives in the warzone. Since 2003, more than 330 explosive ordnance disposal (EOD) robots have been shipped to Iraq and Afghanistan, costing roughly US 150000 dollars each. The robots are tested to gauge their effectiveness and speed in a variety of environments and terrains. Efforts are underway to develop better navigation tools and appendages that allow the robots to manipulate explosives with more dexterity